Analisis Pengaruh Modal Sendiri Dan Modal Kredit Terhadap Peningkatan Usaha Home Industry Kripik Ubi Dihitung Dari Tingkat Profitabilitas (Studi Kasus Industri Rumahan Desa Karanglo Kecamatan Tawangmangu) - Tyaningsih, Kris; , Drs. Agus Mugorobin, M.M (2017)
This study aims to determine the effect of equity and loan capital to the increased effort home industriy potato chips from the level seen in the village provitabilitas Karanglo Tawangmangu sub-district Karanganyar district. This research is quantitative. The population in this tudy is the home industry is located in the village of Tawangmangu Karanglo District of Karanganyar district amounting to 12 home industry with all the criteria of the sample then there are 6 of the home industry meet the criteria to be sampled. Analysis of the data used in this research is to use a simple linear regression analysis. The results of this study are Equity (X1) effect on profitability (Y). Credit Capital (X2) effect on profitability (Y). The results also show that the effect on profitability of own capital amounted to 11.4% whereas the effect on profitability of credit capital of 10.3%.